I am Malala : the girl who stood up for education and was shot by the Taliban - Yousafzai, Malala (Phoenix, 2014)
When the Taliban took control of the Swat Valley, one girl spoke out. Malala Yousafzai refused to be silenced and fought for her right to an education. On Tuesday October 9, 2012, she almost paid the ultimate price.